Approach to P16 and Ki-67 in the Cervical Intraepithelial Neoplasia staging - Kolotusha, Valeriia; Khoperiya , Viktoriia (The Ukrainian Scientific Medical Youth Journal, 2025)
cervical cancer is a tumor resulting from infection with high-risk human papillomavirus and develops from precursors within the epithelium, which are now referred to as squamous intraepithelial lesions or cervical intraepithelial neoplasias (SIL/CIN). CIN is categorized into CIN1, CIN2, and CIN3 depending on the degree of epithelial involvement. The treatment of patients with pre-invasive cervical lesions relies on the determined histological classification. The primary objective of this study was to thoroughly assess the relevance of immunohistochemical staining for the biomarkers p16 and Ki67 in the evaluation of cervical squamous intraepithelial lesions (SIL). This research aimed to elucidate the relationship between the levels of expression of these biomarkers and the various stages of cervical intraepithelial neoplasia (CIN). By analyzing the correlation between p16 and Ki67 expression and the severity of CIN lesions, the study seeks to enhance the understanding of these immunohistochemical markers' diagnostic and prognostic value in clinical practices for managing HPV-related cervical pathology. Materials and methods. We analyzed cases of women with suspected cervical neoplasia during cytology investigation. H&E-stained and IHC slides of all biopsy samples were reviewed and classified according to the criteria outlined by the LAST project. All histological samples were processed according to routine procedures. Results. We found, that p16 expression is divided into three groups: negative, strong and diffuse block-positive, and focal or patchy positive reaction. In cases histologically classified as CIN1, p16 showed inconsistent positivity with a moderate intensity. The glandular epithelium displayed clear signs of atypia, and p16 revealed inconsistent moderate positivity. Ki-67 was expressed in cells nuclear in the basal and parabasal layers of the squamous epithelium in all CIN stages. The results showed significant p16 and Ki67 expression differences among different groups of CIN. The expression levels of P16 and Ki-67 showed a positive correlation with the severity of cervical lesions and are very helpful for distinguishing CIN1 from CIN2 and CIN3. Conclusions. The expression levels indicating a consistent increase in expression that reflects the progression. Utilizing both P16 and Ki-67 can help identify patients at a higher risk for Squamous Cell Carcinoma (SCC). The applications of p16 and Ki-67 have proven to be important supplementary tools in evaluating the actual characteristics of these lesions. The staining results of p16 and Ki-67 across various histological grades of cervical lesions underscore their usefulness in validating histological diagnoses.